Lithium–Graphite Paste: An Interface Compatible Anode for Solid‐State Batteries. Issue 10 (21st January 2019) - Duan, Jian; Wu, Wangyan; Nolan, Adelaide M.; Wang, Tengrui; Wen, Jiayun; Hu, Chenchen; Mo, Yifei; Luo, Wei; Huang, Yunhui
Abstract: All‐solid‐state batteries (ASSBs) with ceramic‐based solid‐state electrolytes (SSEs) enable high safety that is inaccessible with conventional lithium‐ion batteries. Lithium metal, the ultimate anode with the highest specific capacity, also becomes available with nonflammable SSEs in ASSBs, which offers promising energy density. The rapid development of ASSBs, however, is significantly hampered by the large interfacial resistance as a matched lithium/ceramic interface that is not easy to pursue. Here, a lithium–graphite (Li–C) composite anode is fabricated, which shows a dramatic modification in wettability with garnet SSE. An intimate Li–C/garnet interface is obtained by casting Li–C composite onto garnet‐type SSE, delivering an interfacial resistance as low as 11 Ω cm 2 . As a comparison, pure Li/garnet interface gives a large resistance of 381 Ω cm 2 . Such improvement can be ascribed to the experiment‐measured increased viscosity of Li–C composite and simulation‐verified limited interfacial reaction. The Li–C/garnet/Li–C symmetric cell exhibits stable plating/striping performance with small voltage hysteresis and endures a critical current density up to 1.0 mA cm −2 . The full cell paired with LiFePO4 shows stable cycle performance, comparable to the cell with liquid electrolyte. The present work demonstrates a promising strategy to develop ceramic‐compatible lithium metal‐based anodes and hence low‐impedance ASSBs. Abstract : A lithium–graphite composite with lithiated graphite homogenously dispersed in a lithium matrix is successfully synthesized and shows perfect interfacial compatibility with garnet‐type solid‐state electrolytes. Symmetric cells and full cells equipped with this novel Li–C composite anode deliver much smaller voltage hysteresis and better cyclic stability compared to cells with a pure Li anode, showing promising applications for all‐solid‐state batteries.